Utilization of information technology to support information and knowledge management by law firms in Polokwane City - Bopape, Tsekere Solomon (University of Limpopo (Turfloop Campus), 2009)
This research report serves as an empirical investigation into the utilization of information technology to support information and knowledge management in law firms, as well as an attempt to design an information and knowledge management model for law firms. Members of the legal profession attached to law firms in the Polokwane City were investigated to find out how optimally they utilize information and communication technologies to support information and knowledge management in their daily operations. The research indicated that there are several ways in which information technology could be used to support the creation, organization, and transfer of information and knowledge in law firms, for the benefit of both lawyers and their clients . In order to provide for an empirical basis for this research, a survey research method, through the use of the questionnaires and interviews, was conducted, followed by a detailed content analysis of law firm websites. An in-depth literature review on the utilization of information technology to support information and knowledge management in law firms was also carried out to determine the findings of other studies that have been conducted elsewhere on the current topic. The results of this research showed that lawyers attached to law firms in the city of Polokwane appear to be non-users of information technology in as far as information and knowledge management is concerned. Most of the members of the law firms in the city seem to be utilizing information technology for basic purposes such as word processing, legal research, client billing, and communication through the e-mail. Other information and knowledge management tools, such as intranets, extranets and web portals, appear not to be utilized by most of the law firms in the city. Based on the findings of this research project, an information and knowledge network model, in a form of Wireless Local Area Network for the law firms in the Polokwane City, is proposed. This network could be utilized by law firms operating in the city to deposit, organize, retrieve, and share information and knowledge collaboratively through the use of information technology. Factors that should be taken into consideration in attempting to implement the proposed model are also discussed. At the end of the research report, some recommendations on encouraging lawyers to utilize information technology optimally are provided, together with recommendations for future research.
Thesis (Ph.D. (Information Studies)) --University of Limpopo, 2009
Keywords: Information Technology; Information use; Knowledge management; Lawyers; Information resources -- use studies; Information technology -- South Africa; Law offices; Lawyers -- South Africa